Geospatial and Multivariate Statistical Interpretations for Relationships between Physico-Chemical Properties and Heavy Metals in Some Agricultural Soils of Kalar and Quratoo Sub-Districts, East Iraq - Hayder Mohammed Issa; Azad H. Alshatteri (Eurasian Journal of Science and Engineering, 2020)
In this study, ninety agricultural soil samples were collected from Kalar and Quratoo sub-districts east of Iraq. Where soil samples have been analyzed to quantify concentrations of nine soil physicochemical properties and sixteen heavy metals by using ICP-OES with other analyzing tools. Analysis results showed that significant variations exist in concentrations of the investigated parameters among sampling sites. Multivariate statistics have been conducted to identify relationships between heavy metals and soil properties. Multiple correspondence analysis MCA showed strong relationships for total nitrogen T.N. with Cu, Ni, and Hg. Agglomerative hierarchical clustering (AHC) and factorial analysis (FA) divided soil property relationships with heavy metals into three main categories in terms of heavy metals nature; naturally occurred, generated from anthropogenic sources, and of weak relationships. Spatial variation map showed that soil properties in middle parts of the study area are more impacted by heavy metals that came from anthropogenic sources. This study aids to improve the environmental protection and monitoring of agricultural lands in Iraq.